Carbon Emissions and Life Expectancy in Nigeria - Osabohien, Romanus; Aderemi, Timothy Ayomitunde; Akindele, Dolapo Bose; Jolayemi, Lydia Bose (International Journal of Energy Economics and Policy, 2020)
The Autoregressive Distributed Lag (ARDL) model was applied in the study to examine how energy consumption impacts on life expectancy in Nigeria. Data was sourced from the United States (US) Carbon Dioxide Information Analysis Centre, the Central Bank of Nigeria (CBN) Statistical Bulletin, International Energy Agency (IEA), and the World Development Indicators (WDI) for the period 1980-2017. Findings showed that inter alia; carbon emissions are significant and negatively affect life expectancy. This finding implied that, on average, carbon emissions could reduce life expectancy by 0.35%. Based on this finding, the study concludes by recommending that the Nigerian government should embark on the alternative use of energy that emits lesser carbon. Thus, this will help to attain the sustainable development goals of good health and well-being alongside with affordable, reliable and sustainable use of energy for all. Keywords: Fossil Fuel: Electric Power: Carbon Dioxide, SDG JEL Classifications: P48, Q4 DOI: https://doi.org/10.32479/ijeep.10834